The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s40544-018-0209-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of water-soluble Cu nanoparticles and evaluation of their tribological properties and thermal conductivity as a water-based additive

Abstract: Efficient and sustainable use of water-based lubricants is essential for energy efficiency. Therefore, the use of water-lubricated mechanical systems instead of conventional oil lubricants is extremely attractive from the viewpoint of resource conservation. In this study, water-soluble Cu nanoparticles of size approximately 3 nm were prepared at room temperature (around 25 °C) via in-situ surface modification. The tribological behavior of the as-synthesized Cu nanoparticles as an additive in distilled water wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Further investigation suggested that such an ultrathick tribofilm dominated by Pd/S compounds is responsible for the superior lubricating behavior, as shown in Fig. 14. Zhao et al [163] prepared water-soluble Cu nanoparticles of size approximately 3 nm at room temperature via in-situ surface modification. The tribological behavior of such Cu nanoparticles as an additive in distilled water can significantly improve the tribological properties of distilled water and the lowest friction coefficient of 0.06 was obtained via lubrication with a concentration of 0.6 wt% of Cu nanoparticles in distilled water, which is a reduction of 80.6% compared with that obtained via lubrication with distilled water alone.…”
Section: Inorganic Additivementioning
confidence: 99%
“…Further investigation suggested that such an ultrathick tribofilm dominated by Pd/S compounds is responsible for the superior lubricating behavior, as shown in Fig. 14. Zhao et al [163] prepared water-soluble Cu nanoparticles of size approximately 3 nm at room temperature via in-situ surface modification. The tribological behavior of such Cu nanoparticles as an additive in distilled water can significantly improve the tribological properties of distilled water and the lowest friction coefficient of 0.06 was obtained via lubrication with a concentration of 0.6 wt% of Cu nanoparticles in distilled water, which is a reduction of 80.6% compared with that obtained via lubrication with distilled water alone.…”
Section: Inorganic Additivementioning
confidence: 99%
“…Many nanomaterials are beneficial for improving tribological properties of water-based lubricants [6][7][8]. Graphene and graphene oxide [9][10][11], carbon dots [12], hard carbon spheres [13], carbon nanotubes [14], ionic liquids [15], sulfides [16][17][18], oxides [2,7,19], and metal nanocopper [20,21] have been designed and synthesized to improve the performance of water. Furthermore, a number of lubrication mechanisms have been proposed to explain the improvement of tribological performance, including: (a) formation of physical or/and chemical tribofilms.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Minakov et al [46] used CuO nanoparticles, modified with xanthan gum polymers, as nano-fluid additives and demonstrated a significant increase in the heat transfer coefficient and the coefficient was proportional to the concentration of CuO additive. Previous studies have demonstrated that nanomaterials with good thermal conductivity can accelerate heat transfer and reduce localized high temperatures of frictional surfaces [18,21].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the lowest friction coefficient of 0.06 was obtained via lubrication with a concentration of 0.6 wt% of Cu nanoparticles in distilled water. 13 Unfortunately, the large volume and poor dispersion stability of BN is a severe limitation in the application of water-based lubricant additives. 14,15 Li et al had investigated the nanoscale tribological properties of hexagonal boron nitride nanosheets (BNNS) deposited on a silicon oxide substrate.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zhao et al had prepared water‐soluble Cu nanoparticles. The results showed that the lowest friction coefficient of 0.06 was obtained via lubrication with a concentration of 0.6 wt% of Cu nanoparticles in distilled water . Unfortunately, the large volume and poor dispersion stability of BN is a severe limitation in the application of water‐based lubricant additives …”
Section: Introductionmentioning
confidence: 99%